Samuelson on Induced Innovation: Rejoinder: Agreements, Disagreements, Doubts, and the Case of Induced Harrod-Neutral Technical Change - Samuelson, Paul A. (The Review of Economics and Statistics, 1966)
Paul A. Samuelson, Samuelson on Induced Innovation: Rejoinder: Agreements, Disagreements, Doubts, and the Case of Induced Harrod-Neutral Technical Change, The Review of Economics and Statistics, Vol. 48, No. 4 (Nov., 1966), pp. 444-448